2020
DOI: 10.1186/s12960-020-00468-w
|View full text |Cite
|
Sign up to set email alerts
|

Can traditional bonesetters become trained technicians? Feasibility study among a cohort of Nigerian traditional bonesetters

Abstract: Background: Traditional bonesetters (TBS) provide the majority of primary fracture care in Nigeria and other lowand middle-income countries (LMICs). They are widely patronized and their services are commonly associated with complications. The aim of the study was to establish the feasibility of formal training of TBS and subsequent integration into the healthcare system.Methods: Two focus group discussions were conducted involving five TBS and eight orthopaedic surgeons in Enugu Nigeria. Audio-recordings made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Patronage of traditional medical services, especially bone-setters, is widespread in Ghana and other LMICs due to ready availability within communities, apparently low direct cost to patients, and a deep cultural acceptance for their services within the society. [20][21][22][23] Patrons who have had any form of acceptable results from previous experiences with traditional medicine might try the service again when they need it. Conversely, individuals who did not initially receive formal health care for injuries such as a fractured bone may experience substantial delays and associated morbidity and disability when formal care is finally sought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patronage of traditional medical services, especially bone-setters, is widespread in Ghana and other LMICs due to ready availability within communities, apparently low direct cost to patients, and a deep cultural acceptance for their services within the society. [20][21][22][23] Patrons who have had any form of acceptable results from previous experiences with traditional medicine might try the service again when they need it. Conversely, individuals who did not initially receive formal health care for injuries such as a fractured bone may experience substantial delays and associated morbidity and disability when formal care is finally sought.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nigeria reported the willingness of traditional bone-setters to undergo some formal training to improve their knowledge and skills. 23 †No member of the reference group would engage in a potentially harmful practice only for the particular injury type. ‡None would engage in a potentially harmful practice only for the particular injury type.…”
Section: Unweightedmentioning
confidence: 99%
“…Thus, TBH has "high patronage and confidence in their communities as about 70-90% of primary fracture care is provided by the TBH in many rural communities in Nigeria." 28 One reason for this patronage is the cultural belief that ailments most often have spiritual components that need to be cured by supernatural means-such as incantations and concoctions. These superstitious means cannot be provided by conventional surgeons.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%
“…16,17 They are not regulated, and thus, quality may be questionable. [19][20][21] In addition to the aforementioned, they hardly refer cases beyond them to hospitals. 11,22 Notwithstanding the shortcomings, there is still a high rate of acceptance and patronage among the populace.…”
Section: Introductionmentioning
confidence: 99%